ECOLOGICAL CONSUMER CHOICES AND INCOME LEVELS: A SUSTAINABLE CONSUMPTION PERSPECTIVE - Klaudia Juszczuk (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2025)
Sustainable consumption is a key component of global strategies aimed at environmental protection and combating climate change. Modern society faces the challenge of mitigating the negative impact of consumption on the natural environment, which requires both a change in attitudes and a modification of consumption habits. The aim of this study was to assess the relationship between income levels and eco-friendly consumer choices in the context of households. The study focused on households in rural areas of the Lublin Voivodeship. A proprietary questionnaire, administered using the CAWI method, was employed as the research instrument. The study was conducted from 3 July to 25 August 2024 and involved 203 respondents. One of the significant aspects of sustainable consumption is the selection of organic products that are produced in a manner that minimizes their negative impact on the environment. However, consumer decisions in this regard are strongly influenced by income levels. The research findings indicate that eco-related consumption decisions are highly dependent on both household size and the perceived level of affluence. Larger families are more likely to engage in environmentally conscious purchasing, although they still encounter numerous obstacles, such as insufficient labeling of organic products or inappropriate pricing. These results underscore the necessity of implementing measures to enhance label transparency and standardize the pricing of organic products, which could contribute to increased acceptance and popularity among consumers.